Effect of sodium butyrate and zinc sulphate supplementation on recombinant human IFN  production by mammalian cell culture - Zuqueli, Romina (2006)
Recombinant human interferon-β1 (rhIFN-β1) glycoprotein is used as a therapeutic agent for a variety of diseases, such as multiple sclerosis and hepatitis. In the present work, different strategies were applied to produce rhIFN-β1a in mammalian cell cultures. Transfected population of CHO-K1, CHO dhfr-, BHK and HEK cells were compared for their ability to produce rhIFN-β1a, and clones of the most promising cell line (CHO-K1) were isolated by the limit dilution method. Likewise, different culture conditions were assayed by changing the amounts of fetal calf serum, sodium butyrate and/or ZnSO4, to improve cell productivity. The presence of each additive increased the rhIFN-β1a yield ranging from 2 to 8 times, depending on the tested cell clone, but when these components were simultaneously added to the medium, the rhIFN-β1a concentration in the supernatants was even greater.